Role of internal controls in business resilience and growth of small businesses in Gaborone - Tangirala, Suryakanthi (Archives of Business Research, 2019)
This study was carried out to evaluate whether internal controls have an implication in the resilience and growth of small businesses in Gaborone. The study was driven by the fact that small managed businesses lack internal controls in their businesses thus hindering their growth which has a negative impact on their lifespan and sustainability. The scope of the study was limited to small businesses in Gaborone. The outcome of the study will be useful by relevant authorities by knowing the factors that affect the use of internal controls so as to put controls in place and the results will help to scrutinize the organizational internal controls thus paving way for growth and survival. Primary data was used, which were questionnaires handed out to small businesses and the data collected from the companies under study was calculated and analysed using Microsoft Excel. Data processed was presented in bar charts, pie charts and tables. The results showed that internal controls have an effect in the resilience and growth of small businesses.